Students’ patriotic values formation by means of a foreign language as an important issue - Larina , Tatiana Vladimirovna; Sukhanova, Anastasiia Sergeevna; Kodirov, Bakhtiyor Rozikovich; Kuchinskaya, Elizaveta Alexandrovna; Borisova, Elena Vladimirovna (International Journal of Psychosocial Rehabilitation, 2020)
The research is relevant due to the necessity to prepare devoted specialists who are able to act according to society’s values, and ready to work for the good of the country. Thus, the article focuses on the specifics of students’ patriotic values formation. The key element here is a foreign language course at University that offers all necessary facilities for the conditions for the personal values formation. Therefore, it is important to look into this formation process by means of a foreign language. The purpose of the research is to analyze some practical aspects while using didactic materials with a patriotic approach. We state that axiological potential should be engaged. And thus a specially prepared set of didactic materials is recommended. The main scientific approaches are: axiological, personality-oriented and systematic. Besides, theoretical and empirical methods have been used. The method of generalization and synthesis of value formation experience was applied while analyzing psychological and pedagogical literature on the research topic. The interview and pedagogical observation methods allowed the value formation process to be analyzed. In order to conduct experimental work didactic materials contributing to the students’ patriotic values formation have been prepared. The article presents the analysis of various studies on value formation. This has enabled didactic materials to be clearly structured. Information blocks (a text with the set of tasks) are included in the course of the lessons. The texts are about important events, traditions, heroic deeds of past years and contemporary ones. The experimental research work has shown that didactic materials with valuable and patriotic approach are quite effective for patriotic values formation. The results of the article will be helpful for teachers of higher education and researchers of value formation.